Development of a Non-financial Reporting for Oil Сompanies - R. G . Kaspina; Z. A. Chistopolova (Учёт. Анализ. Аудит, 2022)
The article discusses the development of non-financial reporting of companies in the oil sector from the standpoint of increasing stakeholder interest in non-financial information itself and the need for its consistency and comparability. We analyzed the standards for the formation of non-financial reporting used by organizations in the oil industry because of the most significant impact of their activities on climate change. We considered 12 global companies included in the Oil and Gas Climate Initiative (OGCI) and three Russian companies as a factual basis for the study. As a result of analyzing the main non-financial reporting standards used by the oil sector organizations, we identified the most and the least popular reporting standards. It substantiated the reasons for the choice of certain non-financial reporting standards and the need for the transition of the system of non-financial reporting of oil companies to a unified format.Methods of analysis, comparison and description of non-financial reporting standards created by oil companies became the methodological tool for conducting the study.